Main etiological agents identified in 170 men with urethritis attended at the Fundação Alfredo da Matta, Manaus, Amazonas, Brazil - de Souza, Lucilene Sales; Sardinha, José Carlos; Talhari, Sinésio; Heibel, Marcel; Santos, Mônica Nunes dos; Talhari, Carolina (Anais brasileiros de dermatología, 2021)
Sexually transmitted infections (STI) are a global public health problem. Urethritis are among the most common STIs, and can cause several complications and facilitate the transmission of the HIV virus. To investigate the main etiologic agents of urethritis in 170 men treated at Fundação Alfredo da Matta. To identify the agents, urethral exudate and urine were collected. Gram and culture tests were performed in Thayer-Martin medium for Neisseria gonorrhoeae and polymerase chain reaction for Neisseria gonorrhoeae, Chlamydia trachomatis, Trichomonas vaginalis, Ureaplasma urealyticum, Ureaplasma parvum, Mycoplasma hominis, Mycoplasma genitalium, and herpes simplex types 1 and 2. N. gonorrhoeae were identified in 102 (60.0%) patients, C. trachomatis in 50 (29.4%), U. urealyticum in 29 (17.0%), M. genitalium in 11 (6.5 %), U. parvum in ten (5.9%), and M. hominis in seven (4.1%). Herpes simplex type 2 was diagnosed in 24 (21.6%) of the 111 patients who underwent PCR for this pathogen. In 69 cases there was co-infection; the most frequent were: N. gonorrhoeae and C. trachomatis in 21 (14.7%) patients; N. gonorrhoeae and C. trachomatis in 21 (12.4%) patients; N. gonorrhoeae and herpes simplex type 2 in 11 (6.5%), and N. gonorrhoeae and U. urealyticum in nine (5.3%). Not relevant. N. gonorrhoeae, C. trachomatis, U. urealyticum, and herpes simplex type 2 were the pathogens most frequently identified in the present study. The main coinfection found was N. gonorrhoeae and C. trachomatis. T. vaginalis and herpes simplex type 1 were not identified in any of the patients.